Hak Anak setelah Perceraian Akibat Pertengkaran Suami Istri - Debora Purba; Elvi Zahara (Universitas Medan Area, 2017)
The Rights of the Child After Divorce Due to the Sparring of the Wife Marriage is a human desire to let go of solitude in navigating the twists and turns of life. Marriage generally applies to every creature created by God, both humans, plants and animals. In essence marriage is a sense of love, obligation, fulfillment of sexual desire and continuation of offspring. Rights of minors after divorce, parents must maintain and educate their children as well as possible. In article 4 of the Marriage Law, fathers are responsible for all the costs of care and education of children needed, if the father cannot fulfill his obligations, the court can determine that the mother also bears the costs of care and education for the child also divorced. The purpose of this study is; to find out custody of minors due to divorce from a married couple; to know the judges' judgment in determining child care responsibilities. This type of research is normative juridical, descriptive analytical nature, and data sources for this research are obtained through secondary data, namely data collected through document studies on the language library.